The Allelic Variant A391T of Metal Ion Transporter ZIP8 (SLC39A8) Leads to Hypotension and Enhanced Insulin Resistance - Verouti, Sophia N.; Pujol-Giménez, Jonai; Bermudez-Lekerika, Paola; Scherler, Laeticia; Bhardwaj, Rajesh; Thomas, Aurélien; Lenglet, Sébastien; Siegrist, Mark; Hofstetter, Willy; Fuster, Daniel G.; Hediger, Matthias A.; Escher, Geneviève; et al. (Frontiers in Physiology, 2022)
The metal ion transporter ZIP8 (SLC39A8) mediates cellular uptake of vital divalent metal ions. Genome-wide association studies (GWAS) showed that the single-nucleotide polymorphism (SNP) variant A391T (rs13107325) is associated with numerous human traits, including reduced arterial blood pressure, increased body mass index and hyperlipidemia. We analyzed in vitro the transport properties of mutant ZIP8 A391T and investigated in vivo in mice the physiological effects of this polymorphism. In vitro, the intrinsic transport properties of mutant ZIP8 were similar to those of wild type ZIP8, but cellular uptake of zinc, cadmium and iron was attenuated due to reduced ZIP8 plasma membrane expression. We then generated the ZIP8 A393T mice (ZIP8KI) that carry the corresponding polymorphism and characterized their phenotype. We observed lower protein expression in lung and kidney membrane extracts in ZIP8KI mice. The ZIP8KI mice exhibited striking changes in metal ion composition of the tissues, including cobalt, palladium, mercury and platinum. In agreement with GWAS, ZIP8KI mice showed reduced arterial blood pressure. Body weight and plasma lipid composition remained unchanged, although these features were reported to be increased in GWAS. ZIP8KI mice also exhibited remarkable insulin resistance and were protected from elevated blood glucose when challenged by dietary sucrose supplementation. We showed that increased hepatic insulin receptor expression and decreased ZnT8 (slc30a8) metal ion transporter mRNA expression are associated with this phenotypic change. In conclusion, our data reveal that ZIP8 plays an important role in blood pressure regulation and glucose homeostasis.